Teknologi Televisi Digital - Nick Soedarso (Bina Nusantara University, 2011)
Television is the most common medium for people to update the latest information around the world, for more than fifty years. Now, the development of television has grown rapidly to present a picture, even to bring fun to watch movies at home. With HDTV technology, consumers can now enjoy more highly detailed images to be enjoyed with family. This article is based on literature study, on printed and electronic references. The higher the TV resolution does not mean that the picture performance will be better. For HD format, there are 720 vertical lines; meanwhile for full HD there are 1080 vertical lines. TV in low resolution perhaps having good picture quality, but not all the luxury could be enjoyed in details like in HD or full HD format.